Walking in the Forbidden City: embodied encounters in narrative geography. Issue 2 (3rd April 2018) - Liu, Peng
Abstract : This paper engages contemporary literature from body studies to situate the Confucian body and its interactions with the space of the Forbidden City. The analysis demonstrates how discomfort, anxiety and the restraining of the body unfold through embodied encounters in the space. The paper focuses on the limits to what is possible in the movements of body, and how these movements rely upon and resist the space promised by Confucian thought. Understood as an embodied activity, walking is mobilised in this investigation by comparing the journey to meet the emperor taken by eunuchs and provincial officials in Imperial times and my own bodily experience in contemporary time.